Development and application of a simulation scenario for transient tachypnea of the newborn nursing care - Hwang, Ju Hee (Edelweiss Applied Science and Technology, 2024)
This study was conducted to develop and implement Transient tachypnea scenario of the for nursing student, and examine its effects on nursing performance, communication skill and learning confidence. Using the nonequivalent comparison group post-test non-synchronized design method, the research subjects were composed of total 54 people including 28 subjects for experimental group and 26 subjects for comparison group. Using the IBM SPSS v. 25.0 for data analysis, the differences in the baseline characteristics of both groups were tested through the t-test, X2-test, and Fisher’s exact test. Results: The results of this study are as follows. As a result of conducting a homogeneity test on the experimental group and comparison group, there was no difference between the two groups. The experimental group who participated in practice education using the Transient tachypnea scenario simulator was statistically significant in nursing performance (F=4.092, p<.001), communication skills (F=2.879, p=.002), and learning confidence (F=.289, p=.001). These findings indicated that simulation based Transient tachypnea scenario education program is effective educational strategy for nursing students to nursing performance and communication skills, learning satisfaction.